Physical Activity Levels, Frequency, and Type Among Adolescents with and Without Autism Spectrum Disorder. - Stanish, Heidi; Curtin, Carol; Must, Aviva; Phillips, Sarah; Maslin, Melissa; Bandini, Linda (Journal of Autism & Developmental Disorders, 2017)
We compared time spent in moderate and vigorous physical activity (MVPA), type, and frequency of participation in physical activities between adolescents with ASD (n = 35) and typically developing (TD) adolescents (n = 60). Accelerometers measured MVPA and participants were interviewed about engagement in physical activities. Adolescents with ASD spent less time in MVPA compared to TD adolescents (29 min/day vs. 50 min/day, p < 0.001) and fewer met the Physical Activity Guidelines for Americans (14 vs. 29%, p > 0.05). Among adolescents <16 years old, those with ASD participated in fewer activities than TD adolescents (5.3 vs. 7.1 activities, p < 0.03). Walking/hiking and active video gaming were among the top activities for both groups. Findings support the need for interventions that meet the needs of youth with ASD.